The Met Office convective‐scale ensemble, MOGREPS‐UK. (11th October 2017) - Hagelin, Susanna; Son, Joohyung; Swinbank, Richard; McCabe, Anne; Roberts, Nigel; Tennant, Warren
Abstract : Since 2012 the Met Office has been running a short‐range convective‐scale ensemble prediction system over the United Kingdom, known as MOGREPS‐UK. In this article we consider MOGREPS‐UK in its past, present and future configurations. We describe the evolution of the system during its first few years as an operational model and explain the rationale behind its development. The operational configuration of MOGREPS‐UK is evaluated using neighbourhood verification techniques which allow the comparison of ensemble and deterministic forecasts in a probabilistic sense. We compare the performance of MOGREPS‐UK to that of the higher‐resolution UK deterministic convective‐scale model, the UKV, and show that over a 3‐month long trial MOGREPS‐UK performs better for all variables considered. Plans of future upgrade options of MOGREPS‐UK that take advantage of the increased computing capacity at the Met Office are discussed. Three different options are compared: increasing the domain size (now implemented), decreasing the horizontal grid‐spacing, and increasing the number of ensemble members. Objective verification results from month‐long winter and summer trials show that all options have their benefits, with the most improvement seen with the increase in ensemble size, particularly for precipitation. Abstract : This paper presents the evolution of MOGREPS‐UK, the Met Office convective‐scale ensemble prediction system, and its applications. The paper also contains an evaluation of the current system using neighbourhood verification and presents possible future upgrades to the ensemble.